2009
DOI: 10.1158/0008-5472.can-09-1934
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipocalin 2 Impairs Breast Tumorigenesis and Metastasis

Abstract: Lipocalin 2 (LCN2; also known as NGAL) is a secreted glycoprotein and its elevated expression has been observed in breast cancers. However, the importance of LCN2 in breast tumorigenesis is unclear. Here, we employed a spontaneous mammary tumor mouse model showing that MMTV-ErbB2 (V664E) mice lacking mouse LCN2 had significantly delayed mammary tumor formation and metastasis with reduced matrix metalloproteinase-9 activity in the blood. LCN2 expression is upregulated by HER2/phosphoinositide 3-kinase/ AKT/NF-κ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
182
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(194 citation statements)
references
References 19 publications
11
182
1
Order By: Relevance
“…LCN2 is a member of the lipocalin family composed of small extracellular proteins that transport and present ligands to cell surface receptors, and form macromolecular complexes, thus playing important roles in cell regulation, proliferation and differentiation (Flower, 1994). LCN2 can enhance tumor growth and metastasis by protecting matrix metalloproteinase-9 from degradation and by increasing angiogenesis and/ or by promoting the epithelial to mesenchymal transition, which is associated with breast cancer progression (Leng et al, 2009;Yang et al, 2009). Therefore, this study identified a novel gene regulatory pathway (NFAT5 stimulation of S100A4 and LCN2 genes) that is coactivated by ddx5/ddx17 and that, together with previously reported ddx5 and ddx17 target genes like cyclin D1 and Snail (Shin et al, 2007;Yang et al, 2007;Carter et al, 2010), strengthens the role of ddx5 and ddx17 in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 is a member of the lipocalin family composed of small extracellular proteins that transport and present ligands to cell surface receptors, and form macromolecular complexes, thus playing important roles in cell regulation, proliferation and differentiation (Flower, 1994). LCN2 can enhance tumor growth and metastasis by protecting matrix metalloproteinase-9 from degradation and by increasing angiogenesis and/ or by promoting the epithelial to mesenchymal transition, which is associated with breast cancer progression (Leng et al, 2009;Yang et al, 2009). Therefore, this study identified a novel gene regulatory pathway (NFAT5 stimulation of S100A4 and LCN2 genes) that is coactivated by ddx5/ddx17 and that, together with previously reported ddx5 and ddx17 target genes like cyclin D1 and Snail (Shin et al, 2007;Yang et al, 2007;Carter et al, 2010), strengthens the role of ddx5 and ddx17 in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the UPR in cancer cells also upregulates lipocalin 2 (81), an innate immune inflammatory molecule whose first described function is the prevention of iron scavenging by bacterial siderophores (82). Notably, spontaneous breast cancer in mice showed a decreased rate of progression in Lcn2-deficient mice (83,84).…”
Section: Upr-linked Effects On Immunoregulatory Signalsmentioning
confidence: 99%
“…Of these genes, LCN2, a gene associated with breast cancer metastasis, was upregulated two-to fourfold in the absence of NFAT3 (data not shown). LCN2 has been implicated in the formation of metastases in murine breast cancer models (Shi et al, 2008;Leng et al, 2009;Yang et al, 2009) and it has been identified as one of the genes downregulated in ERA þ breast cancers (Stoesz et al, 1998). To validate the results from our gene chip analysis, we performed quantitative real-time PCR (Q-PCR) on total RNA from the ERA þ T-47D breast cancer cells.…”
Section: Nfat3 Inhibits the Expression Of Lcn2mentioning
confidence: 99%
“…High LCN2 expression levels are associated with malignancy in different cancers including ovarian (Lim et al, 2007), pancreatic (Furutani et al, 1998), lung and colon cancers (Friedl et al, 1999). Recently, LCN2 has been implicated in tumorigenesis and formation of metastases in murine breast cancer models (Shi et al, 2008;Leng et al, 2009;Yang et al, 2009). A potential function for LCN2 in the migratory capacity of colon cells (Playford et al, 2006) and tissue invasion by leukemia cells (Leng et al, 2008) has also been documented.…”
Section: Introductionmentioning
confidence: 99%